2018
DOI: 10.1007/s10461-018-2094-5
|View full text |Cite
|
Sign up to set email alerts
|

Travel Time to Clinic but not Neighborhood Crime Rate is Associated with Retention in Care Among HIV-Positive Patients

Abstract: Using geospatial analysis, we examined the relationship of distance between a patient's residence and clinic, travel time to clinic, and neighborhood violent crime rates with retention in care or viral suppression among people living with HIV (PLWH). For HIV-positive patients at a large urban clinic, we measured distance and travel time between home and clinic and violent crime rate within a two block radius of the travel route. Kruskal-Wallis rank sum was used to compare outcomes between groups. Over the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…This may be due to a number of interrelated factors relating to structural inequality and racialized experiences with healthcare. For example, neighbourhoods in Chicago with higher proportion Black inhabitants tend to be further from HIV care (85). This distance to HIV care is associated with poor retention in care (85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to a number of interrelated factors relating to structural inequality and racialized experiences with healthcare. For example, neighbourhoods in Chicago with higher proportion Black inhabitants tend to be further from HIV care (85). This distance to HIV care is associated with poor retention in care (85).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neighbourhoods in Chicago with higher proportion Black inhabitants tend to be further from HIV care (85). This distance to HIV care is associated with poor retention in care (85). Other barriers related to structural inequality that disproportionately impact Black populations are access to private insurance, housing insecurity, and incarceration (20,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Patients' addresses were geocoded and the travel distance and travel time to the clinic as well as the crime rate along the travel rate were calculated. Geocoding methods have been previously described 28 . Using data from the American Community Survey (US Census Bureau), characteristics of a patient's community at the census tract level including racial composition, fraction of population on Supplemental Nutrition Assistance Program, commute characteristics and education levels were collected 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that transportation barriers have a significant impact on health outcomes, particularly among disadvantaged individuals [32,33]. Regarding HIV care and treatment, travel time has been found to be a barrier to retention in care [34,35].…”
Section: Discussionmentioning
confidence: 99%